How to draw histories? art as method - Sanathanan, T. (Seagull Foundation for Arts, Calcutta, 2017)
The Sri Lankan civil war that came to a violent end in 2009 was, in a way, a product of ideological fix and the methodological limitation of written history of the Island. In the post-armed-conflict context, historical narratives of dominance have been further strengthened by monumentalization/ memorialization projects of military victory. In the process of narrating this victory, the history of civilians who carried the burden of the war has been completely erased. This presentation discusses four art projects: ‘ History of Histories’(2004), ‘Imag(in)ing Home’ (2009), ‘ The Incomplete Thompu’(2011) and ‘ The Cabinet of Resistance’(2016) that dealt with the memory of civilians caught in the civil war. These works employed art as a tool of collecting, archiving and narrating the experience of war through ordinary mundane material.
Keywords: Race; Sinhalese Buddhist; History; Memory; Civil War